Functional and pasting properties of a tropical breadfruit (Artocarpus altilis) starch from Ile-Ife, Osun State, Nigeria - Akanbi, Taiwo Olusesan; Saari, Nazamid; Adebowale, A. A. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
This study was carried out to determine the proximate, functional and pasting properties of breadfruit starch. Breadfruit starch was isolated from matured breadfruit (Artocarpus altilis) and was analyzed for its functional, proximate and pasting properties. The starch contains 10.83%, 0.53%, 0.39%, 22.52%, 77.48% and 1.77% moisture, crude protein, fat, amylose, amylopectin and ash contents respectively. The average particle size, pH, bulk density and dispersibility of the breadfruit starch were 18 μm, 6.5, 0.673 g/mls, and 40.67% respectively. The swelling power of the breadfruit starch increases with increase in temperature, but there was a rapid increase in the swelling power from 70 to 80°C. The pasting temperature of the starch paste was 84.05°C, setback and breakdown values were 40.08 and 7.92 RVU respectively. The peak viscosity value was 121.25 RVU while final viscosity value was 153.42 RVU. This study concluded that breadfruit starch has an array of functional, pasting and proximate properties that can facilitate its use in so many areas where the properties of other starches are acceptable.